1995
DOI: 10.1002/rcm.1290090409
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel nucleotides found in the red seaweed Porphyra umbilicalis

Abstract: Extracts of the red seaweed Porphyra umbilicalis are a valuable constituent of herbal medicines. The nucleotide complement of such an extract was purified and compounds identified by chromatographic behaviour, UV absorbance/pH profile, base-to-phosphate ratio, acid hydrolysis, and by fast-atom bombardment mass spectrometry with mass-analysed ion kinetic energy spectrum scanning. In addition to eighteen common nucleotides, and two cyclic nucleotides, fifteen novel nucleotides were identified, comprising eight d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Ionization methods commonly used such as fast atom bombardment (FAB) [13,14] matrix-assisted laser desorption ionization (MALDI) [15] and electrospray ionization (ESI) [16]. In the field of nucleotide chemistry, static fast atom bombardment mass spectrometry (FAB-MS) was a monumental step forward, and its potency for the identification of cyclic nucleotides was demonstrated by Newton et al [13,17,18]. Witters et al [19] showed that cyclic nucleotides (among cAMP and cGMP), can be identified using specific collision-activated dissociation (CAD) fragments as diagnostic ions.…”
Section: Introductionmentioning
confidence: 99%
“…Ionization methods commonly used such as fast atom bombardment (FAB) [13,14] matrix-assisted laser desorption ionization (MALDI) [15] and electrospray ionization (ESI) [16]. In the field of nucleotide chemistry, static fast atom bombardment mass spectrometry (FAB-MS) was a monumental step forward, and its potency for the identification of cyclic nucleotides was demonstrated by Newton et al [13,17,18]. Witters et al [19] showed that cyclic nucleotides (among cAMP and cGMP), can be identified using specific collision-activated dissociation (CAD) fragments as diagnostic ions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently enzymes concerned with the metabolism and action of cyclic nucleotides are important pharmacological targets. Application of qualitative fastatom bombardment (FAB) mass spectrometry (MS) with mass-analysed ion kinetic energy (MIKE) spectrum scanning has proved invaluable in the identification of endogenous cyclic nucleotides 1-3 and of their analogues 4,5 and derivatives, 6-8 by virtue of the characteristic fragmentations 9,10 observed in the MIKE spectra obtained after collisionally-induced dissociation (CID) of the protonated molecule in the FAB mass spectrum. The advantage of softionization methods such as FAB is the production of cyclic nucleotide mass spectra without a requirement for derivatization and, combined with CID/MIKE analysis, this permits the differentiation of the 3',5'-cyclic nucleotides, 9,10 which are the biochemical second messengers, from the 2',3'-cyclic nucleotide isomers, which are merely intermediates of nucleic acid catabolism.…”
mentioning
confidence: 99%
“…[33d, 35,36] These characteristic features also apply for our derivatives, both protected phosphorylated (19,20,25,26) and sodium salts (31,32), as shown in Table 1.…”
Section: Synthesis Of Tetrakis Phosphorylated Monosaccharidesmentioning
confidence: 86%
“…[25] 3',5'-PP nucleotide derivatives phosphorylated at position 2' have been isolated from the red seaweed Porphyra umbilicalis, which is a constituent of herbal medicines. [26] Finally, several 3',5'-deoxyribose phosphate and PP nucleotides were proven to be human P2Y6 receptor ligands, P2Y1 receptor antagonists and partial agonists, and recombinant rat P2X receptor agonists and antagonists. [27,28] In the work presented herein, we targeted polyphosphates (with three or more phosphate groups) and seven-and/or eight-membered cyclic PPs of hexopyranoses, which are all novel compounds, except one.…”
Section: Rationalementioning
confidence: 99%